Rice husk and charred husk amendments increase porewater and plant Si but water management determines grain As and Cd concentration - Linam, Franklin; Limmer, Matt A.; Tappero, Ryan; Seyfferth, Angelia L. (Plant and soil, 2022)
Purpose Rice is a staple crop worldwide and a silicon (Si) hyperaccumulator with Si levels reaching 5–10% of its mass; this can result in desilication and Si-deficiency if plant residues are not managed correctly. Rice is also uniquely subject to arsenic (As) and cadmium (Cd) contamination depending on soil conditions. Our goal is to quantify the effects of rice husk (a Si-rich milling byproduct) amendments and different water management strategies on rice uptake of Si, As, and Cd. Methods We employed 4 husk amendment treatments: Control (no husk), Husk (untreated husk), Biochar (husk pyrolyzed at 450 °C), and CharSil (husk combusted at > 1000 °C). Each of these amendments was studied under nonflooded, alternate wetting and drying (AWD), and flooded water management in a pot study. Porewater chemistry and mature plant elemental composition were measured. Results Husk and Biochar treatments, along with flooding, increased porewater and plant Si. Vegetative tissue As decreased with increasing porewater Si, but grain As and plant Cd were primarily controlled by water management. Grain As and Cd were inversely correlated and are simultaneously minimized in a redox potential (Eh) range of 225–275 mV in the studied soil. Ferrihydrite in root iron plaque decreased As translocation from porewater to grain, but amendments were not able to increase plaque ferrihydrite content. Conclusion We conclude moderate husk amendment rates (i.e., 4 years’ worth) with minimal pretreatment strongly increases rice Si content but may not be sufficient to decrease grain As in low Si and As soil.